A COMPARATIVE METHOD OF IOT ARCHITECTURES, CHALLENGES, PRIVACY AND SECURITY ISSUES - Maheswari, Ramisetti Uma; Mareeswari, V (The journal of contemporary issues in business and government, 2021)
It has been anticipated that all the different things of our surroundings to be under the internet. At current internet is a global network of computing or computer devices. The Idiom IoT is the scope of the internet is to be prolonged outside computer devices being interconnected to different things. Internet of Things is a categorization or classification where interconnects these non-living things like devices that can club together then try to communicate or to establish a protocol between them that they can effectively communicate among themselves and they can perform in a good manner without human intervention. As of now there is no efficient usage of IoT framework due to its now and then remodeling strategies, Due to heavy usage of IoT framework there is lot more to concern about security and privacy. This particular article deals with various IoT framework and their working and challenges of IoT framework.